KKN-PPM KKN-PPM Meningkatkan Personal Income dan Pengembangan Olahraga pada Generasi Muda Desa - Firmansyah Dahlan (Jurnal Berkarya Pengabdian Masyarakat, 2020)
The main problems of the young generation of Muhajirin village; First, personal income. 1) Lack of employment because they only rely on the planting and harvesting season, they become manual laborers in nearby cities; 2) Increased of crime rates involving the younger generation after the reduced employment opportunities; 3) It is difficult for the younger generation to prepare for the future or to help their family in economy matter. Second, related to the field of sports. 1) The younger generation is prone to falling into negative activities such as promiscuity, narcotics, criminal problems and fighting between youths thus, sports can be a solution to these problems; 2) Negative activities decreasing the health status of the Young Generation, especially at school age and have an impact on decreasing interest and learning outcomes; 3) There is no interest in the Young Generation of Muhajirin Village in developing traditional sports. This program is implemented in 2 (two) activity cycles; First, empowering the younger generation to increase personal income in the form of training and workshops as an effort to create an atmosphere or climate which allows the potential of the community to develope (enabling), strengthening the potential or power of the community (empowering), and empowering also means protecting. Second, the development of sports achievement is expected to provide positive energy for the younger generation, improving the fitness and health level of the younger generation, introducing traditional sports. Third, partnerships in business linkages, either directly or indirectly, based on the principles of mutual need, trust, strengthening and benefit. Realization of activities in the form of: 1) Youth organization training, entrepreneurship, creative economy, online business, and procurement of appropriate technology; 2) Community service with the Youth and Community in establishing and improving adequate sports infrastructures; 3) Sub-district and village scale sports events.